Experiments and Numerical Simulations of Diluted Spray Turbulent Combustion Proceedings of the 1st International Workshop on Turbulent Spray Combustion - Merci, Bart.; Roekaerts, Dirk.; SADIKI, AMSINI; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This book reflects the outcome of the 1st International Workshop on Turbulent Spray Combustion held in 2009 in Corsica (France). The focus is on reporting the progress of experimental and numerical techniques in two-phase flows, with emphasis on spray combustion.  The motivation for studies in this area is that knowledge of the dominant phenomena and their interactions in such flow systems is essential for the development of predictive models and their use in combustor and gas turbine design. This necessitates the development of accurate experimental methods and numerical modelling techniques.  The workshop aimed at providing an opportunity for experts and young researchers to present the state-of-the-art, discuss new developments or techniques and exchange ideas in the areas of experimentations, modelling and simulation of reactive multiphase flows. The first two papers reflect the contents of the invited lectures, given by experts in the field of turbulent spray combustion. The first  concerns computational issues, while the second deals with experiments. These lectures initiated very interesting and interactive discussions among the researchers, further pursued in contributed poster presentations. Contributions 3 and 4 focus on some aspects of the impact of the interaction between fuel evaporation and combustion on spray combustion in the context of gas turbines, while the final article deals with the interaction between evaporation and turbulence.
Preface --  Issues in Computational Studies of Turbulent Spray Combustion, by  E. Gutheil --  Details and Complexities of Boundary Conditions in Turbulent Piloted Dilute Spray Jets and Flames , by A.R. Masri and J.D. Gounder --  Toward The Impact of Fuel Evaporation-Combustion Interaction on Spray Combustion in Gas Turbine Combustion Chambers. Part I: Effect of  Partial Fuel Vaporization on Spray Combustion, by A. Sadiki, W. Ahmadi,  M. Chrigui and J. Janicka --  Toward The Impact of Fuel Evaporation-Combustion Interaction on Spray Combustion in Gas Turbine Combustion Chambers. Part II: Influence of High Combustion Temperature on Spray Droplet Evaporation, by A. Sadiki, W. Ahmadi and  M. Chrigui --  Reynolds Stress and PDF Modeling of Two-Way Coupling and Vaporisation Interaction in a Turbulent Spray Flame, by N.A. Beishuizen and D. Roekaerts.
Keywords: Fluid mechanics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Phase transitions (Statistical physics).; Energy systems; Physical measurements; Measurement .; Fluids; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Phase Transitions and Multiphase Systems; Energy Systems; Measurement Science and Instrumentation; Fluid- and Aerodynamics